Educação, democracia e escola em tempos sombrios: neoconservadorismo na educação brasileira - Albuquerque, José Eduardo Brum de (2019)
Brazil goes through a delicate moment in its history. Democracy has been systematically attacked through projects of a totalitarian and authoritarian nature, directly affecting different institutions, especially the school. This work is a descriptive research of a qualitative nature that aims to analyze some aspects of current Brazilian education, especially the politics of deconstruction underway, promoted by conservative governments. We highlight in this analysis the projects of the School without Party, the BNCC and the Reform of Secondary School. The objective of the research is to analyze the implications of the school, and especially the teacher, considering its role as a pillar of the process of democratization and humanization of individuals and the rescue of citizenship. The research aims to question the reasons why conservative projects such as those above, can be welcomed by a large part of the population, including a significant group of teachers. The discussion takes into account, as a counterpoint, democracy as conceived by Dewey, when it speaks of democracy as a social or moral idea and as a way of life, and Freire, when he refers to democracy as a collective achievement that demands respect, dialogue and decision-making power to all who participate in education, resizing the role of agents involved in the educational process. The conclusion points to a great challenge that the school and teachers will have in the struggle for a democratic and humanistic education in this scenario.